The Cult of Saints among Muslims and Jews in Medieval Syria - Atif Khalil (International Institute of Islamic Thought, 2004)
Contemporary Jewish-Muslim relations are so mired in the Middle East’s political conflict that most people are often quite surprised to learn of the remarkable theological, legal, and mystical intersections between both traditions. Modern political hostilities centered on the Palestinian-Israeli divide have almost entirely clouded the shared Semitic heritage of faiths that were, until just a little more than 50 years ago, invariably stamped by the Christian West with the seal of “otherness” – an “internal otherness” in the case of Judaism, and an “external otherness” in the case of Islam. In this light, Josef Meri’s work is a welcome contribution to the scholarly study of Jewish-Muslim relations. The study raises our awareness of both religions’ common cultural and intellectual history: more specifically, to the medieval Muslim and Jewish pilgrimage culture of saint veneration in Syria, and, to a lesser extent, other regions of the Near East. The work grew out of the author’s doctoral dissertation at Oxford, done under the supervision of Wilferd Madelung and Daniel Frank, and bears the mark of the many hours Meri must have spent as a scholarly archeologist digging through an enormous range of classical Arabic and Hebrew texts as well as pertinent secondary literature. Although the concentration of the comparative analysis tilts toward the Islamic side (the author notes that the evidence for Jewish saint veneration is considerably less), he still manages to explore the parallel concepts, religious practices, and architectural facets relevant to his analysis with reasonable success. The work is not simply a descriptive account of Jewish and Muslim saint veneration, but an assessment of the psychological and cultural modes that accompany such forms of religious expression. To this end, Meri draws out some of the wider theoretical issues pertaining to the construction of sacred space and the social function of saints and pilgrimage sites ...